TPACK in context: An updated model - Dominik Petko; Punya Mishra; Matthew J Koehler (Computers and Education Open)
The Technological Pedagogical and Content Knowledge (TPACK) framework has evolved significantly since its introduction, particularly in its treatment of context. The original model acknowledged contexts through a dotted circle surrounding the framework's core components; however, understanding and operationalizing these contexts has remained challenging for researchers and practitioners. We address this challenge by proposing a new conceptual synthesis that bridges two prominent approaches to context in TPACK: contexts as external influences and Contextual Knowledge (XK) as a distinct knowledge domain. We argue that both perspectives are essential and complementary. Drawing on research from cognitive psychology, teacher expertise, and situated learning, we argue that TPACK exists simultaneously as teacher knowledge that is shaped by external contexts (contextualized knowledge) and as knowledge about educational environments (Contextual Knowledge). This dual nature is reflected in our proposed model, which maintains the original framework's dotted circle representing external contexts while incorporating XK as an additional knowledge domain. This reconceptualization provides theoretical clarity and practical utility for understanding how teachers develop and apply their technology integration knowledge across different educational settings.